(untitled) (Academicia Globe: Inderscience Research, 2021)
Vitiligo is the most common depigmentation disorder where the selective destruction of functioning melanocytes causes depigmentation of the skin, hair and mucosal surfaces. It affects approximately 0.5% to 1% of the population, with an average age of onset at about 24 years, its prevalence appears to be equal between men and women and there is no difference in the rate of occurrence according to skin type or race. Several etiological factors have been suggested for which the most compelling evidence involves a combination of environmental, genetic and immunological factors interacting to contribute to autoimmune melanocyte destruction. Vitiligo is a common skin disorder characterized by depigmented white patches in the skin due to loss of melanocytes. It remains unclear what causes damage or death to the melanocytes, there are many potential pathophysiological theories involving autoimmune, neural, autocytotoxic, biochemical, oxidative stress, melanocytorrhagy, and decreased melanocyte survival hypotheses. Autoimmune theory is more prominent in generalized vitiligo, which is considered a complex disorder involving combined pathogenic effects of multiple susceptibility genes and unknown environmental factors that lead to autoimmune destruction of melanocytes.